SYSTEM ADMINISTRATION STUDENT REGISTRATION AND CONTRIBUTION MONTHLY COURSES IN DANCE STUDIO SANGGAR ESPE APPLICATIONS USING MICROSOFT VISUAL BASIC 6.0 - Fipit Aprilyanthi; Ire Puspa Wardhani SKom, MMSI (Jurnal Sistem Informasi, 2002)
At this writing, the authors take the title "Pendafdtaran Administration System andthe Student Course Fee Monthly Dance Studio in Studio ESPE using MicrosoftVisual Basic 6.0 Applications". Sanggar has now stepped forward, we need a goodmanagement in managing these centers.In a dance studio, searching and data processing have many different ways. It can beseen from the system of registration and monthly fees they run, whether the system isstill using manual or computer means terisasi. But at this point the studio is masihgusing manual method, whereas today the technology is getting advanced.For that would be nice if the system enrollment and monthly dues that are still using amanual developed through a computerized system. Because the registration systemand computerized monthly dues will be effective and efficient in searching and dataprocessing, so that the data did not overlap with other data and in preparing theinformation needed does not require a long time.